Inclusive Classroom Management In Non-Inclusive Preschool (Case Study At TK it Ihya Assunah Tasikmalaya) - Salsabila, Nala; Huda, Nida Fajriatul; Rizal, Soni Samsu (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
Inclusive education is a fundamental right of every child, including those with learning, emotional, or behavioral challenges. However, many early childhood institutions are not formally inclusive. This study aims to explore how a non-inclusive preschool, TK IT Ihya Assunah in Tasikmalaya, implements inclusive classroom management for children with mild to moderate special needs. A qualitative case study approach was employed, involving classroom observations, in-depth interviews with teachers, and documentation analysis. The findings reveal that although the school is not officially inclusive, it adopts inclusive practices through individualized support, structured environments, and responsive teaching strategies. The Beyond Centers and Circle Time (BCCT) learning model is utilized to stimulate child development and foster participation. This study highlights the importance of adaptive management and collaborative support to ensure quality early childhood education for all learners.